Evaluation of the geotouristic attractions from the Wojcieszów area - Muszer, Jolanta; Muszer, Antoni (Geotourism/Geoturystyka, 2018)
The paper presents the results of geological and landscape studies in the Wojcieszów area (the Kaczawskie Mountains), which include investigation, inventory, documentation and a fi rst of its kind evaluation of its geotourism objects. This area has high values of the natural environment and a rich geodiversity associated with a complicated geological structure (the Kaczawa unit, the metamorphic Kaczawa Complex). Some of the anthropogenic activities (mining), which have revealed interesting fragments of the geological structure, have also infl uenced the increase of geotourism attractions in this area. The area is one of the best examples of the region in the Sudetes, where economic considerations predominate over the protection of the natural environment. Since the 16th century, the crystalline Wojcieszów limestone was mined in numerous quarries (e.g. Silesia, Gruszka, Połom, and Miłek). In the limestone, intensive karst processes occurred mainly in the Paleogene (numerous caves and speleothems). As a result of economic activity, some of the caves had been permanently destroyed and the former “Połom” nature reserve was liquidated in the late 1970s. Currently, the only nature reserve is the “Góra Miłek in Wojcieszów”. The area around Wojcieszów is rich in numerous quarries, where other construction materials were obtained (e.g. phyllites, greenschists, and metarhyodacites). Since the 12th to 20th centuries, copper ore was also exploited (adits and shafts) in the Żeleźniak massif (east of Wojcieszów in the Radzimowice area). In the 20th century, uranium ore was mined at t Chmielarz Hill adit. Recently, the Cambrian limestones (Połom) and Quaternary deposits (Okrajnik, Stara Kraśnica) have been exploited. Paradoxically, economic activity, which caused destruction of some protected objects, has also enriched the geodiversity the Wojcieszów region. The results of the evaluation proved the signifififi cant geotouristic potential of the studied area. The most attractive geosites around Wojcieszów demonstrate typical lithologies of the Kaczawa Succession and depict the pre-Variscan geological evolution of the area. // W artykule przedstawiono wyniki badań geologicznych i krajobrazowych rejonu Wojcieszowa (Góry Kaczawskie), które obejmowały inwentaryzację, dokumentację i pierwszą waloryzację jego obiektów geoturystycznych. Obszar ten jest cenny pod względem przyrodniczym oraz charakteryzuje się bogatą georóżnorodnością, związaną ze skomplikowaną budową geologiczną (metamorfi k kaczawski, kompleks kaczawski). Na wzrost walorów geoturystycznych tego obszaru wpłynęły też niektóre działania antropogeniczne (górnictwo), które odsłoniły ciekawe fragmenty budowy geologicznej. Okolice Wojcieszowa stanowią jeden z najlepszych w Sudetach przykładów regionu, w którym względy gospodarcze przeważają nad ochroną przyrody. Już w XVI wieku zaczęto w okolicy wydobywać wapień krystaliczny zwany wojcieszowskim, odsłonięty w licznych kamieniołomach (np. Silesia, Gruszka, Połom, Miłek). W wapieniach krystalicznych miały miejsce intensywne procesy krasowe, które zachodziły głównie w paleogenie (bardzo liczne jaskinie, szata naciekowa). Na skutek działalności gospodarczej część jaskiń została bezpowrotnie zniszczona, a dawny rezerwat przyrody „Góra Połom” został zlikwidowany pod koniec lat 70. Obecnie jedynym rezerwatem jest „Góra Miłek w Wojcieszowie”. W okolicach Wojcieszowa występują liczne łomy, w których pozyskiwano inne surowce budowlane (m.in. fyllity, zieleńce, metaryodacyty). Od XII do XX wieku w masywie Żeleźniaka (na wschód od Wojcieszowa w rejonie Radzimowic) eksploatowano również rudy miedzi (sztolnie i hałdy). W XX wieku poszukiwano rud uranu (sztolnia na Chmielarzu). Współcześnie eksploatowane są kambryjskie wapienie (Połom) oraz osady czwartorzędowe (Okrajnik, Stara Kraśnica). Paradoksalnie, działalność gospodarcza, niszcząc niektóre obiekty chronione, jednocześnie wpłynęła pozytywnie na wzrost georóżnorodności w rejonie Wojcieszowa. Wyniki ewaluacji udowodniły znaczący potencjał geoturystyczny badanego obszaru. Zaproponowano najbardziej atrakcyjne obiekty geoturystyczne okolic Wojcieszowa, przedstawiające litologię dolnej części sukcesji kaczawskiej i ukazujące przedwaryscyjską ewolucję tego obszaru.